A conceptual model for measuring service quality in education - Abdullah, Kalthom (s.n, 2013)
Research on service quality has been an area of interest for many scholars over the last few decades. These studies came in the spot light when Parasuraman et al. (1985) introduced a multi-item scale for measuring service quality;SERVQUAL. It was revisited by many others using different industries than the one used by Parasuraman et al. Later, SERVPERF was introduced by Cronin and Taylor (1992) using the dimensions of SERVQUAL. Similarly, AIRQUAL was introduced by Ekiz et al. (2006) using both SERVQUAL and SERVPERF. The present research attempted to introduce, test and validate another scale: EDUQUAL using some important dimension of SERVQUAL and SERVPERF in the education sector